Die Wirkung von Rumpf-Stabilisationsübungen mit einem Gymnastikball mit oder ohne Elektromyographie-Biofeedback bei Patienten mit chronischen Rückenschmerzen: eine experimentelle Studie - Ahmed, H.; Shaphe, Md. A.; Iqbal, A.; Khan, A. R.; Anwer, S. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2016)
Objective: To investigate the effects of trunk stabilization exercise in combination with EMG biofeedback on transverse abdominis (TrA) activation capacity in patients with chronic low back pain (CLBP).Methods: Ninety patients with CLBP participated to the study: 45 patients were randomly allocated to trunk stabilization exercises combined with EMG biofeedback, and the other 45 patients were allocated to trunk stabilization exercises with no EMG biofeedback. The primary outcome was TrA activation capacity, and the secondary outcomes were pain and the functional disability.Results: Both the group has shown significant improvements in all the outcomes (p<0.05). However, in the EMG biofeedback group, the improvement of TrA activation capacity was higher at week 6 and 8 compared to other group (p<0.05). Similarly, a higher reduction of functional disability was noted at week 6 and 8 in EMG biofeedback group (p<0.05). In addition, a greater reduction of pain intensity was noted at week 8 in EMG biofeedback group (p<0.05).Conclusions: The addition of EMG biofeedback to trunk stabilization exercises compared to trunk stabilization exercises alone has shown greater gains in TrA activation capacity, reduction in pain intensity, and disability in patients with chronic low back pain.
Keywords: exercise therapy; low back pain; musculoskeletal diseases; pain; physiotherapy; rehabilitation